Revolutionizing Onsite Management Using a Cutting-Edge App - Khan, Furqan Faiyaz; Parkar, Fauwaz (Universitas Sulawesi Tenggara, 2023)
Due to lack of adequate material management systems, construction projects often suffer material wastes, delays and other related problems. In order to address the issue of construction material mismanagement, it is envisaged to develop an android application using innovative technologies such as Java, Dart, YAML, Kotlin and Flutter 2.x with Economic Order Quantity (EOQ) and flat fees method as the logical framework. Features such as material list, stock management, purchase records along with supplier information, material issuance records and due amount information is conceived to a part of this versatile tool, capable of overcoming a multitude of challenges, including tracking and managing issued materials on site, maintaining up-to-date stock records, financial tracking, managing supplier information, ensuring accurate and detailed information on material quantities to name a few. Thus, a potential savings of up to 12-15% in material management cost is estimated through the employment of this application on construction projects